The Burden of Drug-Resistant Tuberculosis in Papua New Guinea: Results of a Large Population-Based Survey. - Paul Aia; Margaret Kal; Evelyn Lavu; Lucy N John; Karen Johnson; Chris Coulter; Julia Ershova; Olga Tosas; Matteo Zignol; Shalala Ahmadova; Tauhid Islam (PLoS ONE)
Background Reliable estimates of the burden of multidrug-resistant tuberculosis (MDR-TB) are crucial for effective control and prevention of tuberculosis (TB). Papua New Guinea (PNG) is a high TB burden country with limited information on the magnitude of the MDR-TB problem. Methods A cross-sectional study was conducted in four PNG provinces: Madang, Morobe, National Capital District and Western Province. Patient sputum samples were tested for rifampicin resistance by the Xpert MTB/RIF assay and those showing the presence of resistance underwent phenotypic susceptibility testing to first- and second-line anti-TB drugs including streptomycin, isoniazid, rifampicin, ethambutol, pyrazinamide, ofloxacin, amikacin, kanamycin and capreomycin. Results Among 1,182 TB patients enrolled in the study, MDR-TB was detected in 20 new (2.7%; 95% confidence intervals [CI] 1.1-4.3%) and 24 previously treated (19.1%; 95%CI: 8.5-29.8%) TB cases. No case of extensively drug-resistant TB (XDR-TB) was detected. Thirty percent (6/20) of new and 33.3% (8/24) of previously treated cases with MDR-TB were detected in a single cluster in Western Province. Conclusion In PNG the proportion of MDR-TB in new cases is slightly lower than the regional average of 4.4% (95%CI: 2.6-6.3%). A large proportion of MDR-TB cases were identified from a single hospital in Western Province, suggesting that the prevalence of MDR-TB across the country is heterogeneous. Future surveys should further explore this finding. The survey also helped strengthening the use of smear microscopy and Xpert MTB/RIF testing as diagnostic tools for TB in the country.